دور مرتكزات الايصاء الواسع في تعزيز الانشطة الترويجية : دراسة استطلاعية لآراء عينة من رؤساء الأقسام في معمل الغزل و النسيج /الموصل - نوال حازم جاسم (PROSPECTIVE RESEARCHES, 2023)
Business imposes its effects on the organizations working in its environment and causes them to find best means to be engaged with. In an attempt to do so, these organizations have adopted the idea of mass customization pillars as a means and an approach to enter these business environments. However, the reality of the businesses environment is full of data contributing in the performance of many activities and work. This fact evoked the researcher and led him to raise the following questions: Do heads of departments in spinning and weaving factory have an idea about the concept of mass customization and do they know how to apply this concept and its pillars? The researcher conducts a questionnaire as a tool to collect the data of this phenomenon. Some statistical methods were used to analyze the data collected. Finally, the researcher comes up with some conclusions; the most important one is that there is a correlation and effect between mass customization pillars and business activities to a certain percentage.